Space Time Fractional Telegraph Equation and its Application by Using Adomian Decomposition Method - Manzoor Ahmad; Altaf Ahmad Bhat; Renu Jain (Journal of New Theory)
The telegraph equations are a pair of linear differential equations which describe the voltage andcurrent on an electrical transmission line with distance and time. In this paper the authors give a briefoverview of fractional calculus and extend its application to space-time fractional telegraph equation by usingAdomian decomposition method. The time- space derivates are considered as Caputo fractional derivate. Thesolutions are obtained in the series form.